Suitability of Different Methods for Measuring Black Carbon Emissions from Marine Engines - Päivi Aakko-Saksa; Niina Kuittinen; Timo Murtonen; Päivi Koponen; Minna Aurela; Anssi Järvinen; Kimmo Teinilä; Sanna Saarikoski; Luis M. F. Barreira; Laura Salo; Panu Karjalainen; Ismael K. Ortega; et al. (Atmosphere, 2021)
Black carbon (BC) emissions intensify global warming and are linked to adverse health effects. The International Maritime Organization (IMO) considers the impact of BC emissions from international shipping. A prerequisite for the anticipated limits to BC emissions from marine engines is a reliable measurement method. The three candidate methods (photoacoustic spectroscopy (PAS), laser-induced incandescence (LII), and filter smoke number (FSN)) selected by the IMO were evaluated with extensive ship exhaust matrices obtained by different fuels, engines, and emission control devices. A few instruments targeted for atmospheric measurements were included as well. The BC concentrations were close to each other with the smoke meters (AVL 415S and 415SE), PAS (AVL MSS), LII (Artium-300), MAAP 5012, aethalometers (Magee AE-33 and AE-42), and EC (TOA). In most cases, the standard deviation between instruments was in the range of 5–15% at BC concentrations below 30 mg Sm−3. Some differences in the BC concentrations measured with these instruments were potentially related to the ratio of light-absorbing compounds to sulphates or to particle sizes and morphologies. In addition, calibrations, sampling, and correction of thermophoretic loss of BC explained differences in the BC results. However, overall differences in the BC results obtained with three candidate methods selected by the IMO were low despite challenging exhaust compositions from marine diesel engines. Findings will inform decision making on BC emission control from marine engines.